(untitled) (Journal of Industrial and Mechanical Engineering, 2019)
In the framework of the investigation about noise in Provincial Route No. 4 and the effects on the neighbors, it is that the sectors where the noise measurements were made will be identified, the values obtained will be indicated and mentioned the legislation on the subject. As next actions, the results will be evaluated and the actions to be followed to mitigate this contaminant will be determined.